1992
DOI: 10.1103/physrevlett.68.596
|View full text |Cite
|
Sign up to set email alerts
|

Continuum damping of high-mode-number toroidal Alfvén waves

Abstract: An asymptotic theory is developed to determine the continuum damping of short-wavelength toroidal Alfven eigenmodes, which is essential for ascertaining thresholds for alpha-particle-driven instability in ignited tokamaks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
106
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(108 citation statements)
references
References 8 publications
(7 reference statements)
2
106
0
Order By: Relevance
“…(10). The behavior of local TAE solutions has been obtained in previous works [1,7,8,17,18] and shows ' p;u () e (i 0 jj) which has a \fast" variation in and an exponentially decaying behavior at jj ! 1 , where the local eigenfrequency 0 !qR=V A ' 1=2, and 0 < < 0 = r 0 =R.…”
Section: Numerical Proceduresmentioning
confidence: 64%
See 1 more Smart Citation
“…(10). The behavior of local TAE solutions has been obtained in previous works [1,7,8,17,18] and shows ' p;u () e (i 0 jj) which has a \fast" variation in and an exponentially decaying behavior at jj ! 1 , where the local eigenfrequency 0 !qR=V A ' 1=2, and 0 < < 0 = r 0 =R.…”
Section: Numerical Proceduresmentioning
confidence: 64%
“…[15] in application to the study of ballooning modes, and in Ref. [16] to the study of TAE, where many results of previous work [1,7,8,17,18] were recovered.…”
Section: Introductionmentioning
confidence: 89%
“…For example toroidal geometry influences both mode structures of Toroidal Allven Eigenmodes (TAE) [18] as well as their resonant absorption due to the nonlocal couphng with the s.A. continuum [19,20]. A large variety of Alfvenic oscillations are observed experimentally and there exists an entire "zoology" for their classification based on empirical observations [21].…”
Section: Collective Behaviors and Fast Ion Transportmentioning
confidence: 99%
“…43 Experiments showed that modes with low toroidal mode number n are stabilized when the mode frequency intersects the Alfvén continuum, 44,45 as predicted by continuum damping theory. 46,47 Local stability estimates suggested that coupling to kinetic Alfvén waves~"radiative" damping 48 ! was the dominant damping mechanism and accounted for the observed range of unstable toroidal mode numbers.…”
Section: Iva Toroidicity Induced Alfvén Eigenmodementioning
confidence: 99%